Pelatihan Kader Kesehatan Jiwa dalam Perawatan Pasien Skizofrenia : a Scoping Review - Darti Darti; M.Fatkhul Mubin; Armin Samiasih; Machmudah Machmudah; Ernawati Ernawati (Universitas Malahayati Lampung, 2026)
ABSTRACT Schizophrenia is a severe mental disorder that requires long-term care and sustained support at the community level. Limited mental health workforce resources and the high burden experienced by families highlight the importance of involving mental health cadres as a key strategy in community-based mental health services. Training for mental health cadres has been reported to enhance their capacity to support the care of patients with schizophrenia; however, the available scientific evidence on this intervention remains scattered and heterogeneous. This scoping review aimed to map the existing scientific evidence on training for mental health cadres in the care of patients with schizophrenia, including the types of interventions, study designs, and reported outcomes. This study employed a scoping review design following the Arksey and O’Malley framework and the Joanna Briggs Institute (JBI) guidelines, with reporting in accordance with PRISMA-ScR. A literature search was conducted across five databases: PubMed, ProQuest, ScienceDirect, DOAJ, and Garuda. Inclusion criteria comprised studies that examined training, education, or capacity-building interventions for mental health cadres within the context of schizophrenia care. The selection process resulted in eight articles, which were analyzed using descriptive and narrative synthesis. The synthesis revealed that most studies employed quasi-experimental and pre-experimental designs. The most common interventions were mental health cadre training and psychoeducation, with outcomes including improvements in cadres’ knowledge, attitudes, skills, perceptions, and self-efficacy. Several studies also reported positive effects on the quality of patient care, medication adherence, and reductions in family burden. Training for mental health cadres and community-based psychoeducational interventions are effective in enhancing cadres’ capacity to support the care of patients with schizophrenia. Nevertheless, limitations in study design indicate the need for further research using more robust methodologies to evaluate the long-term effectiveness of cadre-based interventions. Keywords: Mental Health Cadres, Training, Schizophrenia. ABSTRAK Skizofrenia merupakan gangguan jiwa berat yang memerlukan perawatan jangka panjang dan dukungan berkelanjutan di tingkat komunitas. Keterbatasan sumber daya tenaga kesehatan jiwa serta tingginya beban keluarga menjadikan keterlibatan kader kesehatan jiwa sebagai strategi penting dalam pelayanan kesehatan jiwa berbasis masyarakat. Pelatihan kader kesehatan jiwa dilaporkan berpotensi meningkatkan kapasitas kader dalam mendukung perawatan pasien skizofrenia, namun bukti ilmiah terkait intervensi ini masih tersebar dan beragam. Scoping review ini bertujuan untuk memetakan bukti ilmiah terkait pelatihan kader kesehatan jiwa dalam perawatan pasien skizofrenia, termasuk jenis intervensi, desain penelitian, serta luaran yang dilaporkan. Penelitian ini menggunakan desain scoping review mengikuti kerangka Arksey dan O’Malley serta pedoman JBI, dengan pelaporan sesuai PRISMA-ScR. Pencarian literatur dilakukan pada lima basis data, yaitu PubMed, ProQuest, ScienceDirect, DOAJ, dan Garuda. Kriteria inklusi meliputi studi yang membahas pelatihan, pendidikan, atau capacity building kader kesehatan jiwa dalam konteks perawatan pasien skizofrenia. Proses seleksi menghasilkan delapan artikel yang dianalisis secara deskriptif dan naratif. Hasil sintesis menunjukkan bahwa sebagian besar penelitian menggunakan desain quasi-eksperimental dan pre-eksperimental. Intervensi yang paling dominan adalah pelatihan kader kesehatan jiwa dan psikoedukasi, dengan luaran berupa peningkatan pengetahuan, sikap, keterampilan, persepsi, dan self-efficacy kader. Beberapa studi juga melaporkan dampak positif terhadap kualitas perawatan pasien, kepatuhan pengobatan, serta penurunan beban keluarga. Pelatihan kader kesehatan jiwa dan intervensi psikoedukasi berbasis komunitas terbukti efektif dalam meningkatkan kapasitas kader dalam mendukung perawatan pasien skizofrenia. Meskipun demikian, keterbatasan desain penelitian menunjukkan perlunya studi lanjutan dengan metodologi yang lebih kuat untuk menilai efektivitas jangka panjang intervensi berbasis kader. Kata Kunci: Kader, Pelatihan, Skizofrenia.